Inhibition of Piezo1 attenuates demyelination in the central nervous system. Issue 2 (9th October 2019) - Velasco‐Estevez, María; Gadalla, Kamal K. E.; Liñan‐Barba, Núria; Cobb, Stuart; Dev, Kumlesh K.; Sheridan, Graham K.
Abstract: Piezo1 is a mechanosensitive ion channel that facilitates the translation of extracellular mechanical cues to intracellular molecular signaling cascades through a process termed, mechanotransduction . In the central nervous system (CNS), mechanically gated ion channels are important regulators of neurodevelopmental processes such as axon guidance, neural stem cell differentiation, and myelination of axons by oligodendrocytes. Here, we present evidence that pharmacologically mediated overactivation of Piezo1 channels negatively regulates CNS myelination. Moreover, we found that the peptide GsMTx4, an antagonist of mechanosensitive cation channels such as Piezo1, is neuroprotective and prevents chemically induced demyelination. In contrast, the positive modulator of Piezo1 channel opening, Yoda‐1, induces demyelination and neuronal damage. Using an ex vivo murine‐derived organotypic cerebellar slice culture model, we demonstrate that GsMTx4 attenuates demyelination induced by the cytotoxic lipid, psychosine. Importantly, we confirmed the potential therapeutic effects of GsMTx4 peptide in vivo by co‐administering it with lysophosphatidylcholine (LPC), via stereotactic injection, into the cerebral cortex of adult mice. GsMTx4 prevented both demyelination and neuronal damage usually caused by the intracortical injection of LPC in vivo; a well‐characterized model of focal demyelination. GsMTx4 also attenuated both LPC‐induced astrocyte toxicity and microglial reactivity within the lesion core. Overall, our data suggest that pharmacological activation of Piezo1 channels induces demyelination and that inhibition of mechanosensitive channels, using GsMTx4, may alleviate the secondary progressive neurodegeneration often present in the latter stages of demyelinating diseases. Main points: Piezo1 negatively regulates central nervous system myelination. Piezo1 antagonist, GsMTx4, enhances myelination and attenuates demyelination. GsMTx4 is neuroprotective and inhibits lysophosphatidylcholine‐induced astrocyte toxicity.